Teaching staff and their role in the adaptation of society in a «smart city» (Gumilyov Journal of Pedagogy, 2025)
The latest strategic path of development of modern cities with a focus on digitalization predetermines the need for citizens to adapt to life in a “smart city”. The process of using digital technologies in various industries and areas of ensuring the lives of city residents contributes to improving the quality of life, but only if everyone is capable of effectively using modern technologies in educational, work and everyday life. In this aspect, a huge role in the adaptation of society to the realities of the “smart city” is given to teaching staff, who throughout a person's life actively participate in his upbringing, training and development.The purpose of this article is to substantiate the role, areas of activity of teaching staff in terms of adapting society to a “smart city”, as well as to designate the content of personal qualities and competencies of modern teaching staff to perform this function.The scientific and practical significance of the study is the systematic substantiation of the concept of “teaching staff” in the context of the concept of a “smart city”, designating the role in the adaptation of citizens to life in it, as well as highlighting the personal qualities and competencies that a modern teacher should have in the context of digitalization. When writing the article, general scientific research methods were used: content analysis, review of scientific publications, analysis of strategic documents regarding the development of “smart cities” in Kazakhstan, etc. The main results of the study include the formation of a new view on the role of teaching staff, establishing a set of its qualities and competencies necessary for educating citizens in the era of digitalization.